2021
DOI: 10.3390/ijms22126344
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Furin Deficiency on Insulin Receptor Processing and Glucose Control in Liver and Pancreatic β Cells of Mice

Abstract: The insulin receptor (IR) is critically involved in maintaining glucose homeostasis. It undergoes proteolytic cleavage by proprotein convertases, which is an essential step for its activation. The importance of the insulin receptor in liver is well established, but its role in pancreatic β cells is still controversial. In this study, we investigated the cleavage of the IR by the proprotein convertase FURIN in β cells and hepatocytes, and the contribution of the IR in pancreatic β cells and liver to glucose hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…72 The less pronounced impairment of pro-insulin receptor cleavage in the liver is supported by observations in mice with liver-specific furin knockout, suggesting a redundant function of other PCs for insulin receptor maturation in this organ. 68 Taken together, this evidence supports the association between furin reduction and diabetes (Figure 3). In an opposite manner, a study with 21 years of follow up demonstrated that baseline plasma furin levels positively correlate with increased risk of diabetes and mortality in humans (Table 2), indicating the role of furin in diabetes development.…”
Section: ■ Diabetes Mellitussupporting
confidence: 83%
“…72 The less pronounced impairment of pro-insulin receptor cleavage in the liver is supported by observations in mice with liver-specific furin knockout, suggesting a redundant function of other PCs for insulin receptor maturation in this organ. 68 Taken together, this evidence supports the association between furin reduction and diabetes (Figure 3). In an opposite manner, a study with 21 years of follow up demonstrated that baseline plasma furin levels positively correlate with increased risk of diabetes and mortality in humans (Table 2), indicating the role of furin in diabetes development.…”
Section: ■ Diabetes Mellitussupporting
confidence: 83%
“…A population‐based prospective study involved subjects at high risk for the development of T2DM and revealed that initial high furin serum levels increased the risk for the development of T2DM and premature mortality 20,24 . Mutation in furin induces propagation of insulin resistance (IR) and T2DM due to association with mutation in the insulin pro‐receptors 25 . Indeed, high circulating furin serum level is correlated with dyslipidemia, high body mass index, and development of metabolic syndrome 26 .…”
Section: Furin and Cardiometabolic Disordersmentioning
confidence: 99%
“…Consequently, furin knockout mice demonstrate impaired insulin content and secretion [ 68 ]. These animals also exhibit abnormal processing of insulin receptor, decreased pancreatic β-cell mass, and proliferation, and ultimately develop progressive, age-dependent glucose intolerance [ 69 , 70 ]. Although the data available on serpinB8 are scant, the restrictive pattern of this serpin’s expression in the pancreas may reflect the function of this molecule to inhibit furin in the islets, thereby implicating it in various aspects of islet biology.…”
Section: The Role Of Clade B Serpins In Diabetesmentioning
confidence: 99%